Design of Assertive Communication Illustration Book as an Educational Media - Masnuna, Masnuna; Qonita, Nyimas (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
Communication is the basis of social interaction activities in everyday life. There are four communication patterns, namely passive communication, aggressive communication, passive-aggressive communication, and assertive communication. Of the several communication patterns, assertive communication is the most effective communication pattern. However, assertive communication is still a common thing among the public. According to questionnaire data, 63.6% of 66 fresh graduates do not know assertive communication. A fresh graduate will be faced with problems such as work problems and other work demands. In addition, it is also necessary to have soft skills that are useful in the future. Therefore, assertive communication patterns are needed in the world of work. Seeing fresh graduates who are busy with work, informative and interesting educational media is needed, namely illustration books. The use of visuals and verbal in this book adjusts the characteristics of the target audience. Based on these phenomena and problems, this research uses the preparation stage and the creation stage. With this illustrated book media, it is hoped that the target audience can apply it in their daily lives, attract reading interest, and be able to work more productively in the future.